Critical thinking about health and treatments in the United States: a cross-sectional assessment of parents and undergraduate college students - Vanesa A. Mora Ringle; Astrid Dahlgren; Sarah Rosenbaum; Amanda Jensen-Doss (BMC Public Health)
Abstract Background There is an urgent need to study and increase the public’s ability to think critically about health and treatments. Unfortunately, we do not currently have a clear, in-depth understanding of critical thinking about health in the United States, especially its rates among parents and college students, two particularly important groups. This study assessed and characterized critical thinking about health with U. S. parents and college students. We also explored whether critical thinking about health varied as a function of sociodemographic determinants. Methods Parents (N = 142) and college students (N = 145) in the U. S. completed an online test of critical thinking about health, and answered questions about their background. Results Both parents and college students in the U. S. struggled to think critically about health and treatments based on various science literacy and evidence-based practice principles. Parents with higher educational attainment had lower critical thinking about health, and college students who reported a liberal political affiliation had higher critical thinking scores. Conclusions This investigation demonstrates a need to increase critical thinking about health among U. S. parents and college students so they can be empowered to make informed health choices.